2019
DOI: 10.1002/aoc.5394
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antioxidant properties of phyto‐synthesized silver nanoparticles using Lavandula stoechas extract

Abstract: Due to environmentally friendly and cost‐ effective issues, biological methods for silver nanoparticles (AgNPs) synthesis are advantageous over chemical and physical ones. In this study, AgNPs synthesized using Lavandula stoechas extract as a reductant and its antioxidant capacity, antibacterial property and cytotoxicity effect were investigated. The phyto‐synthesized AgNPs were characterized using various analyses such as transmission electron microscopy (TEM), scanning electron microscopy (SEM), x‐ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…AgNPs synthesised using Aloin extracted from Aloe barbadensis was evaluated for its cytotoxic potential against MCF-7 cell line which showed an IC 50 value of 22 lg/ml [49] while Das et al [50] reported cytotoxic effect of Ananas comosus mediated synthesised AgNPs against HepG 2 cell lines. Mahmoudi et al [51] reported cytotoxic effect of AgNPs synthesised using Lavandula stoechas extract on RAW264 cell line at 62.5 lg/ml as an effective concentration. In fact, green synthesised AgNPs show promising cytotoxic effect against an array of cell lines like Jurkat, MCF, AGS, Hep3B, MG-63, HT29, U87, A549, HeLa, HeK293, SNO, MKN-28, etc.…”
Section: Cytotoxic Effectmentioning
confidence: 99%
“…AgNPs synthesised using Aloin extracted from Aloe barbadensis was evaluated for its cytotoxic potential against MCF-7 cell line which showed an IC 50 value of 22 lg/ml [49] while Das et al [50] reported cytotoxic effect of Ananas comosus mediated synthesised AgNPs against HepG 2 cell lines. Mahmoudi et al [51] reported cytotoxic effect of AgNPs synthesised using Lavandula stoechas extract on RAW264 cell line at 62.5 lg/ml as an effective concentration. In fact, green synthesised AgNPs show promising cytotoxic effect against an array of cell lines like Jurkat, MCF, AGS, Hep3B, MG-63, HT29, U87, A549, HeLa, HeK293, SNO, MKN-28, etc.…”
Section: Cytotoxic Effectmentioning
confidence: 99%
“…Therefore, alternatives less hazardous and economically viable methods are being explored. Many reports are available on the biogenesis of AgNPs using several plant extracts 25 .…”
mentioning
confidence: 99%
“…The MTT assay is widely used for the analysis of cytotoxicity caused by silver nanoparticles [70,71], and has demonstrated that the cytotoxic effect depends directly on the physical-chemical characteristics of the nanoparticles, their concentration, the exposure time, and the target cell.…”
Section: Toxicity Assessment Of Silver Nanoparticlesmentioning
confidence: 99%